2008
DOI: 10.1097/aog.0b013e31816e34b4
|View full text |Cite
|
Sign up to set email alerts
|

A Simple Clinical Maneuver to Reduce Laparoscopy-Induced Shoulder Pain

Abstract: I.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
134
2
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 119 publications
(149 citation statements)
references
References 24 publications
11
134
2
2
Order By: Relevance
“…Two studies also found a significant reduction in the severity of SP [8,16]. Two studies measured the VAS scores at rest [8,16], and the last study did not report whether they measured the VAS at rest or during cough/mobilisation [5]. The significant effect of PRM on SP severity was found 4-24 h after surgery and 12 h after discharge [16] and at 24 h postoperatively [8].. Two out of three studies reported post-operative analgesic consumption [8,16].…”
Section: Pulmonary Recruitment Manoeuvrementioning
confidence: 88%
See 4 more Smart Citations
“…Two studies also found a significant reduction in the severity of SP [8,16]. Two studies measured the VAS scores at rest [8,16], and the last study did not report whether they measured the VAS at rest or during cough/mobilisation [5]. The significant effect of PRM on SP severity was found 4-24 h after surgery and 12 h after discharge [16] and at 24 h postoperatively [8].. Two out of three studies reported post-operative analgesic consumption [8,16].…”
Section: Pulmonary Recruitment Manoeuvrementioning
confidence: 88%
“…1). Of the included RCTs, six studies evaluated the effect of intraperitoneal local anaesthetics [10][11][12][13][14][15], three studies evaluated the effect of pulmonary recruitment manoeuvre (PRM) [5,8,16] and three studies evaluated the effect of drainage [17][18][19]. The remaining three studies have been grouped together as "other techniques" and evaluated the effect of intraperitoneal saline installation [20], minilaparoscopy [21] and gasless laparoscopy by using Laprolift® [22].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations